2016
DOI: 10.1002/2016pa002968
|View full text |Cite
|
Sign up to set email alerts
|

Intrareef variations in Li/Mg and Sr/Ca sea surface temperature proxies in the Caribbean reef‐building coral Siderastrea siderea

Abstract: Caribbean sea surface temperatures (SSTs) have increased at a rate of 0.2°C per decade since 1971, a rate double that of the mean global change. Recent investigations of the coral Siderastrea siderea on the Belize Mesoamerican Barrier Reef System (MBRS) have demonstrated that warming over the last 30 years has had a detrimental impact on calcification. Instrumental temperature records in this region are sparse, making it necessary to reconstruct longer SST records indirectly through geochemical temperature pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 67 publications
4
51
1
Order By: Relevance
“…In contrast to δ 7 Li values, relationships between carbonate Li/Mg, and to a lesser extent Li/Ca, and temperature have been reported in other studies (Marriott et al, 2004a;Montagna et al, 2014;Case et al, 2010;Bryan and Marchitto 2008;Fowell et al, 2016;Hathorne et al, 2013). For inorganic calcite (Marriott et al, 2004a) and brachiopods (Delaney et al, 1989), Li/Ca ratios exhibit a negative relationship with temperature.…”
Section: Influence Of Temperaturecontrasting
confidence: 60%
See 1 more Smart Citation
“…In contrast to δ 7 Li values, relationships between carbonate Li/Mg, and to a lesser extent Li/Ca, and temperature have been reported in other studies (Marriott et al, 2004a;Montagna et al, 2014;Case et al, 2010;Bryan and Marchitto 2008;Fowell et al, 2016;Hathorne et al, 2013). For inorganic calcite (Marriott et al, 2004a) and brachiopods (Delaney et al, 1989), Li/Ca ratios exhibit a negative relationship with temperature.…”
Section: Influence Of Temperaturecontrasting
confidence: 60%
“…Instead, culture experiments and core top studies have shown that the Li/Ca ratio of foraminifera is influenced by the solution Li/Ca ratio, DIC concentration, and possibly the growth rate (Delaney et al, 1985;Hall and Chan, 2004;Hathorne and James, 2006;Lear and Rosenthal, 2006;Vigier et al, 2015). In contrast, the Li/Mg ratio of corals and foraminifera is more strongly related to temperature than Li/Ca and has been recently proposed as being a reliable proxy for ocean temperature (Bryan and Marchitto, 2008;Case et al, 2010;Montagna et al, 2014;Rollion-Bard and Blamart, 2015;Fowell et al, 2016). The Li/Ca ratio of mollusks might be controlled by a combination of vital effects, growth rate, changes in ocean productivity, and/or dissolution of riverine fine sediments within the ocean (Füllenbach et al, 2015;Thébault et al, 2009;Thébault and Chauvaud, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Montagna et al, 2009). Montagna et al, 2009) but has received more limited use in corals living at higher (i.e., tropical) temperatures (D'Olivo et al, 2018;Fowell et al, 2016;Zinke et al, 2019). Montagna et al, 2009) but has received more limited use in corals living at higher (i.e., tropical) temperatures (D'Olivo et al, 2018;Fowell et al, 2016;Zinke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These issues have prompted the development of alternative paleothermometers, such as Li/Ca (Marriott et al, ) and Li/Mg (Case et al, ; Hathorne, Felis, et al, ; Lear et al, ; Montagna et al, ; see also Fowell et al, ; Marchitto et al, ). Since both Li + and Mg 2+ are not preferentially incorporated into the aragonite lattice ( K D << 1), the ratio of [Li + ]/[Mg 2+ ] remains relatively constant in the calcifying fluid as precipitation proceeds, even though [Ca 2+ ] would be expected to decline (Montagna et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Li/Mg is thought to be largely independent of Rayleigh fractionation and instead should reflect primarily the different temperature sensitivities of Li and Mg to incorporation (Hathorne, Felis, et al, ; Marchitto et al, ; Montagna et al, ). While a general exponential trend exists between Li/Mg and temperature (Marchitto et al, ; Montagna et al, ), some effects of species and location have been reported (Fowell et al, ). Accurate temperature constructions using Li/Mg may therefore require species and possibly site‐specific calibrations (Fowell et al, ).…”
Section: Introductionmentioning
confidence: 99%